IMPLEMENTATION OF SOCIAL RESPONSIBILITY PRINCIPLES IN THE CORPORATE GOVERNANCE SYSTEMS OF AGRIBUSINESS ENTITIES - LYPOVYI, Dmytro; LEPEYKO, Tetyana; DANKEVYCH, Andrii; TYAZHEMOV, Oleksiy (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article is devoted to the study of the principles of social responsibility in the corporate governance systems of agrarian business entities. The topic of the study is extremely relevant and important for ensuring the sustainable development of both individual enterprises and the agrarian sector of Ukraine as a whole. This will contribute to increasing their competitiveness, strengthening their reputation, improving relations with stakeholders and contributing to solving important socio-economic and environmental problems. It has been established that the implementation of the principles of social responsibility in the corporate governance systems of agrarian business entities is not just an ethical choice, but a strategically beneficial and progressive trend. It has been proven that the integration of social, environmental and economic aspects into the process of making managerial decisions allows agrarian enterprises not only to minimize risks and increase their sustainability, but also to strengthen relations with key stakeholders, improve their reputation and increase their competitiveness in the long term. It is determined that taking into account the specifics of the agricultural sector, where activities are directly related to natural resources and rural communities, social responsibility acquires special importance. Responsible land use, careful attitude to the environment, support for the local population and ensuring decent working conditions for employees become key factors in the sustainable development of agricultural business. Thus, the implementation of the principles of social responsibility is an important step towards the formation of an effective and sustainable corporate governance system in the agricultural sector, which contributes not only to the economic prosperity of enterprises, but also to the social and environmental well-being of society as a whole. This is an investment in the future, ensuring the harmonious development of business and the environment.